2019
DOI: 10.3892/mmr.2019.10029
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA AWPPH promotes the proliferation, migration and invasion of ovarian carcinoma cells via activation of the Wnt/β‑catenin signaling pathway

Abstract: The oncogenic role of the long noncoding RNA associated with poor prognosis of hepatocellular carcinoma (lncRNA AWPPH) was reported in various types of malignancies; however, its involvement in ovarian carcinoma (OC) remains unknown. Thus, the present study investigated the role of AWPPH in OC. The expression of AWPPH in tissues and serum acquired from patients with OC, and healthy controls, was determined via reverse transcription-quantitative polymerase chain reaction. The diagnostic value of serum AWPPH exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Next to miRs, several long non-coding RNAs (lncRNAs) have been described to play a causative role in Wnt-associated cell proliferation, EMT, and chemotherapy resistance in ovarian cancer [60,61,62,63,64,65]. Table 1 summarizes the data relative to gene and non-coding RNA alterations leading to Wnt signaling activation in ovarian cancer.…”
Section: Wnt Signaling In Ovarian Cancermentioning
confidence: 99%
“…Next to miRs, several long non-coding RNAs (lncRNAs) have been described to play a causative role in Wnt-associated cell proliferation, EMT, and chemotherapy resistance in ovarian cancer [60,61,62,63,64,65]. Table 1 summarizes the data relative to gene and non-coding RNA alterations leading to Wnt signaling activation in ovarian cancer.…”
Section: Wnt Signaling In Ovarian Cancermentioning
confidence: 99%
“…LncRNAs are involved in a variety of physiological and pathological activities of cells, including proliferation, differentiation, migration, and apoptosis [13][14][15]. Previous studies have revealed that lncRNAs play important roles in osteogenic differentiation of mesenchymal stem [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are involved in a variety of physiological and pathological activities of cells, including proliferation, differentiation, migration and apoptosis [13][14][15] . Previous studies have revealed that lncRNAs play important roles in osteogenic differentiation of mesenchymal stem cells (MSCs) [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%